2021
DOI: 10.1155/2021/9116502
|View full text |Cite|
|
Sign up to set email alerts
|

Neurotransmitters and Electrophysiological Changes Might Work as Biomarkers for Diagnosing Affective Disorders

Abstract: Affective disorders are the leading causes of human disability worldwide; however, the diagnosis is still hard to define, because emotion is the least study subjects in psychology. Recent emotional studies suggest that human emotions are developed from basic emotions, which are evolved for fundamental human lives. Even though most psychologists agree upon the idea that there are some basic emotions, there is little agreement on how many emotions are basic, which emotions are basic, and why they are basic. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In recent years, basic emotion theory has stimulated a number of empirical studies. Thus far, the accepted basic emotions are fear, anger, joy, sadness and disgust [ 14 , 63 ]. However, some psychologists are still debating whether to choose dimensional theory or basic emotional theory.…”
Section: The Similarity Between Personality Traits and Basic Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, basic emotion theory has stimulated a number of empirical studies. Thus far, the accepted basic emotions are fear, anger, joy, sadness and disgust [ 14 , 63 ]. However, some psychologists are still debating whether to choose dimensional theory or basic emotional theory.…”
Section: The Similarity Between Personality Traits and Basic Emotionsmentioning
confidence: 99%
“…Emotion is a very important aspect of personality, and emotions have a similar dimensional construction [ 12 , 13 ]. The dimensional construction theory suggests that emotions are constructed in two dimensions (arousal and valence), and all emotions can be located on the quadrant constructed with two major axes: arousal and valence [ 14 ]. However, personality is much more complicated than emotions; thus, emotional studies might help to shed some light in personality studies.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be called core affects, or prototypical emotions. We also suggested that they are subsided by three monoamine neurotransmitters: dopaminejoy, norepinephrine-fear (anger), and 5-HT-disgust (sadness) (Liang et al, 2021). This theory can be called three primary basic emotion theory (Gu et al, 2019b).…”
Section: Editorial On the Research Topic Uncertainty Induced Emotiona...mentioning
confidence: 99%
“…Even though the last century has witnessed many progresses in emotional studies, psychological analyses have not resolved many of the core issues surrounding emotions (Xu et al, 2022 ), such as the number of basic emotions, and the definition of basic emotions. Although there has been no shortage of psychological research on these debates, for instance, there is little agreement about how many emotions are “basic,” which emotions are “basic,” and why they are “basic” (Liang et al, 2021 ). Anyway, studies of the neural basis of emotions in the brain might resolve these questions.…”
mentioning
confidence: 99%
“…In addition, many recent emotional theories are introduced based on these three monoamines (He et al, 2021 ), including our three primary color model of basic emotions (Gu et al, 2018b ), which proposed that there are only three kinds of basic emotions: disgust, joy, and fear for all the animal kinds. The three basic emotions depend on the monoamine neuromodulators, 5-HT is the substrate for disgust, DA is the substrate for joy; and NE is the neural basis for sympathetic function, and for fear (anger) emotions, for “fight or flight” behaviors (Liang et al, 2021 ).…”
mentioning
confidence: 99%